Inflation and Cash - Popov, Vladimir A. (Journal of Reviews on Global Economics, 2018)
Cash demand is investigated by means of mathematical analysis. The optimal cash amount a person needs in order to minimize the effect of inflation and maximize percent money is given here. The corresponding number of cash transfers for a period is calculated. The corresponding formulas are presented and proved.